2012
DOI: 10.3390/molecules17055255
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of Flavonoids Assayed by Bacterial Reverse Mutation (Ames) Test

Abstract: Abstract:The mutagenicity of ten flavonoids was assayed by the Ames test, in Salmonella typhimurium strains TA98, TA100 and TA102, with the aim of establishing hydroxylation pattern-mutagenicity relationship profiles. The compounds assessed were: quercetin, kaempferol, luteolin, fisetin, chrysin, galangin, flavone, 3-hydroxyflavone, 5-hydroxyflavone and 7-hydroxyflavone. In the Ames assay, quercetin acted directly and its mutagenicity increased with metabolic activation. In the presence of S9 mix, kaempferol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 29 publications
3
76
0
1
Order By: Relevance
“…Eventhough, the tumor volume reduction in TCP-85 and TCP-125 was no significant difference, however this result is remain inconsistence, since the major constituent of TCP is flavonoids. There are various evidences that the proapoptosis effect of flavonoids on tumor cell was in the dose-effect dependent manner 19,20 . Moreover, in the view point of molecular biology this incosistence result possibly associated with DNA unfragmentation and chromatin uncondensation of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Eventhough, the tumor volume reduction in TCP-85 and TCP-125 was no significant difference, however this result is remain inconsistence, since the major constituent of TCP is flavonoids. There are various evidences that the proapoptosis effect of flavonoids on tumor cell was in the dose-effect dependent manner 19,20 . Moreover, in the view point of molecular biology this incosistence result possibly associated with DNA unfragmentation and chromatin uncondensation of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that natural products can represent serious risks to the DNA integrity of different organisms. 31,32 The methodology employed herein affirms that the extract of P. torta is mutagenic in vivo and in vitro in the absence of metabolic activation. The in vivo test would reflect the metabolism of the active constituents and the metabolization is more complex.…”
Section: Mutagenicity Assaysmentioning
confidence: 99%
“…Our results showed that the antimicrobial activity was greater in the bark extracts than that in the leaf extracts. Plants that have flavonoids and tannins with antifungal activity may also exhibit toxicity (Resende et al 2012, Silva et al 2014). Therefore, antimicrobial activity studies must be accompanied by toxicology studies.…”
Section: Resultsmentioning
confidence: 99%